A Conceptual Framework for Investigating Determinants of ESP Learning Outcomes among Students at Vietnamese Universities of Economics and Business - Pham Hong, Nhung; Luong Vu Trong; Linh Nguyen Tung (International Journal of Computational and Experimental Science and Engineering, 2025)
In Vietnam, English for Specific Purposes (ESP) is essential to economic globalisation, and educational institutions are often asked how to optimise ESP learning outcomes. The phrase "factors affecting ESP academic performance" has gained popularity in a number of studies as a response to that query. The paper's primary goal is to identify and evaluate the 5 groups of factors: students’ psycho-cognition, students’ knowledge, lecturer, context and technology. The study was conducted several business and economics majoring universities in Hanoi, Vietnam. The results have indicated that the research model's correctness is guaranteed by the lack of a substantial correlation between the independent variables. According to correlation study, context has little influence on learning outcomes, whereas knowledge and technology have the most effects. ESP researchers, decision-makers, curriculum designers, teachers, and students would all benefit from the findings of this paper.